The relationships between employee occupational self-efficacy, structural empowerment, and work engagement - Žukauskaitė, Irena; Bagdžiūnienė, Dalia; Rekašiūtė Balsienė, Rita (Psichologija, 2019)
Nowadays the competitive advantage of any organization mainly relies not only on technologies or material resources but also on competitive, energetic, engaged employees, who are willing to share their knowledge, skills, and experience. Organizations must not only recruit talents but also inspire them and create the conditions in which they reveal themselves and have the prospect for professional growth. According to Bandura (1982), the personal belief of how well one can execute courses of action required to deal with prospective situations may become crucial for work success. The present study integrates Bandura’s (1982; 1989) Social Cognitive, Kanter’s (1977; 1979) Structural Empowerment, and Schaufeli and Bakker’s(2004) Work Engagement theories and is aimed (1) to analyze the relationships between employee occupational self-efficacy, structural empowerment, and work engagement and (2) to determine the role of occupational self-efficacy in the relationships between the elements of structural empowerment and work engagement. A total of 1636 specialist level employees from one Lithuanian public sector organization were surveyed online. Ninety four percent of the respondents were female, six percent were male. The average age of the respondents was 45.71 (SD = 10.34) years, with the average of 8.29 (SD = 7.23) years of working experience. All respondents had higher education. Occupational self-efficacy was measured using the Schyns & von Collani (2002) OCCSEEF scale (short version), structural empowerment elements (access to opportunity, information, support, and resources, informal power and formal power) were measured using the Conditions of Work Effectiveness Questionnaire – II (CWEQ – II) (Laschinger, Finegan, Shamian, & Wilk, 2001), and the Utrecht Work Engagement Scale (UWES-9) (Schaufeli, Bakker, & Salanova, 2006) was used to measure work engagement. Structural equation modelling (SEM) was applied to determine the mediating role of occupational self-efficacy in the relationships between elements of structural empowerment and work engagement. The analysis revealed that all dimensions of structural empowerment positively predicted occupational self-efficacy, and that occupational self-efficacy positively predicted work engagement. Formal power directly positively predicted work engagement, occupational self-efficacy fully mediated the relationship between informal power and work engagement and partially mediated the relationships between certain predictors (access to opportinity, information, and resources) and work engagement. Despite some limitations (e.g., this being a cross-sectional study, and that specialist level employees were surveyed from one organization), the results of the study highlighted, first, that employee occupational self-efficacy and work engagement might be strengthened by empowering organizational structures, and, second, that occupational self-efficacy is an important personal characteristic explaining the relationships between empowering organizational structures and employee work engagement. Perspectives for future research and practical implications are discussed.